1998
DOI: 10.1007/s004310050969
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled salbutamol and beclomethasone for preventing broncho-pulmonary dysplasia: a randomised double-blind study

Abstract: This randomised prospective trial does not support the use of treatment with inhaled beclomethasone, salbutamol or their combination in the prevention of BPD in premature ventilated neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 24 publications
(34 reference statements)
0
48
0
5
Order By: Relevance
“…Timing of BPD assessment differed across studies. One trial reported BPD at 28 days of age,48 four trials reported this outcome at 36 weeks of postmenstrual/postconceptional age37 38 45 46 and three trials used both timing frames for the diagnosis of BPD 39 43 50. Mortality rate was reported at 28 days of age (two trials),39 48 36 weeks of postnatal age (six trials)37–39 45 46 50 and before discharge (one trial) 43…”
Section: Resultsmentioning
confidence: 99%
“…Timing of BPD assessment differed across studies. One trial reported BPD at 28 days of age,48 four trials reported this outcome at 36 weeks of postmenstrual/postconceptional age37 38 45 46 and three trials used both timing frames for the diagnosis of BPD 39 43 50. Mortality rate was reported at 28 days of age (two trials),39 48 36 weeks of postnatal age (six trials)37–39 45 46 50 and before discharge (one trial) 43…”
Section: Resultsmentioning
confidence: 99%
“…5 Inhaled bronchodilators improve airway resistance but do not reduce the incidence of bronchopulmonary dysplasia. 5,14 These disappointing clinical results may reflect either an intrinsic lack of efficacy of these medications or suboptimal delivery. Thus, we suggest that in future neonatal aerosol studies, particularly studies on nasal CPAP, documentation of drug delivery should be included in the study design.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Parece ser aceptable la oxigenoterapia domiciliaria para disminuir la hipertensión pulmonar y la sobrecarga ventricular derecha manteniendo saturaciones ≥94%, es razonable aceptar que la selección y la toma de decisiones debe ser entonces individualizada.…”
Section: Dr Rogelio Sancho Hernándezunclassified